2009
DOI: 10.1080/19361520802702191
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Minor Sex Trafficking: A Network of Underground Players in the Midwest

Abstract: Trafficking of domestically born children in the United States into the sex trade has been recognized by the U.S. government under the Trafficking Victims Protection Act of 2005. The Midwest has been exposed as a recruitment site for traffickers. Children who have been trafficked into prostitution often experience mental health problems, suffer physical and sexual assaults, have low self-esteem, and are put at risk for HIV/ AIDS and other health problems. This article is based on qualitative interviews with 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 13 publications
2
104
0
Order By: Relevance
“…Traffickers and pimps prey on their vulnerability and lie, coerce, or force adolescents into the commercial sex industry (Cianciarulo, 2008;Williamson & Cluse-Tolar, 2002). Traffickers sometimes pose as peers -friends or boyfriends -who introduce them to the sex trade (Williamson & Prior, 2009). …”
Section: Literature Review Risk Factors For Dmst Victimizationmentioning
confidence: 99%
“…Traffickers and pimps prey on their vulnerability and lie, coerce, or force adolescents into the commercial sex industry (Cianciarulo, 2008;Williamson & Cluse-Tolar, 2002). Traffickers sometimes pose as peers -friends or boyfriends -who introduce them to the sex trade (Williamson & Prior, 2009). …”
Section: Literature Review Risk Factors For Dmst Victimizationmentioning
confidence: 99%
“…Victims of TIP and CSEC have been studied through different sampling methods: snowball or chain referral (Acharya, 2015), respondent-driven (Marcus et al, 2012), convenience (Chin & Finckenauer, 2011), a mix of simulated clients and snowball (Acharya, 2010), target samples (Goldenberg et al, 2015) and samples drawn from institutions (Williamson & Prior, 2009). In this research, we examined 10 identified cases of CSEC survivors sheltered in a not-for-profit institution in Mexico City.…”
Section: The Life Stories Of Survivors Of Csecmentioning
confidence: 99%
“…However, a variety of individuals take part in CSEC. There are direct exploiters such as pimps and sex buyers, as well as traffickers and often their underground networks composed by connectors, transporters, recruiters, traders, "mommies," groomers, bottoms, watchers, and wives-in-law that promote and perpetrate the abuse (for definitions see Chin & Finckenauer, 2011;Territo & Kirkham, 2010;Williamson & Prior, 2009). A recent study in two major U.S. cities, however, found that exploiters tend to act without these support networks (Marcus, Horning, Curtis, Sanson, & Thompson, 2014).…”
Section: Exploiters Indirectly or Directly Involved In Commercial Sexmentioning
confidence: 99%
See 2 more Smart Citations